Impacts of Urban Logistics Measures on Multiple Actors and Decision Layers: Case Study. Issue 1 (January 2015) - Liedtke, Gernot; Matteis, Tilman; Wisetjindawat, Wisinee
An approach for a multiagent model on urban commodity transport is presented. Special attention is paid to the relationship between shippers and carriers. Shippers choose lot sizes, and they commission one or several carriers. Carriers consolidate shipments in hub-and-spoke-transport networks or in en route pickup and delivery tours. Shippers and carriers interact in a transport market where carriers submit offers to the shippers. The effects of urban transport policy measures are transmitted to the ultimate decision makers in transport—the shippers—via prices. Transport tariffs are calculated on the basis of full cost using an activity-based costing schema. The model assesses the effects of a cordon toll in the Tokyo metropolitan area to shippers and carriers. In particular, it analyzes the impacts on market shares and the spatiotemporal structure of truck flows.